A study to assess the knowledge of mothers on home based neonatal care at selected area of rural Bangalore - H., Mohini; B., Sumanth Shetty (International Journal Of Community Medicine And Public Health, 2017)
Background: The new born signifies the beginning of life and provides a foundation for future health of the nation. New born care is strongly influenced by women’s social status, health status, home care practices for mother and new born care services. Therefore, the present study has been designed to assess the Knowledge of mothers on home based neonatal care especially among rural mothers. Methods: After the institutional ethical clearance, five hundred mothers having infants belong to Rural Bangalore were selected by a purposive sampling technique. The structured interview schedule containing demographic variables, knowledge of mothers on home based neonatal care with 27 MCQs having four answers was used. The data collected was analysed using SPSS and minitab. The p value less than 0.05 were considered as the level of significance. Results: Mother’s education, occupation, source of information has highly significant relationship with their knowledge (p=0.01). However, religion and family income of the mothers are not associated with their knowledge (p>0.05). The mother’s knowledge, education, occupation, source of information and dietary pattern have significantly associated with their knowledge on home based neonatal care (p<0.05). Conclusion: 64.6% had moderate, 21.8% had inadequate and 14.2% had adequate knowledge on home based neonatal care. The aspect wise mean knowledge score ranged between 55.3% and 65.3%. Though majority had moderate knowledge on neonatal care, mothers need a regular follow up care in the area of practicing neonatal care.